ETHNOCULTURAL RESOURCE VS. RADICAL ISLAMISM IN THE NORTHERN CAUCASUS - AKAEV, Vakhit; NANAEVA, Boryat (CENTRAL ASIA AND THE CAUCASUS, 2017)
The authors analyze the phenomenon of the so-called radical Islamism, its forms and characteristics in the Northern Caucasus. The paper attempts to address its theoretical foundations, the relationship between Islam and Islamism, and reveals the divergence of the substantive aspects between the two. Particular attention has been paid to the potentials of the traditional ethnic culture of the North Caucasian peoples as a means of opposing radicalism and extremism camouflaged under the cover of Islamic slogans.